Improvizing West Java MSMEs Using Quality Service Gaps Model - H Putri, Afisindika Fadhilah; Novani, Santi (BASKARA : Journal of Business and Entrepreneurship, 2024)
This study aims to understand the challenges and opportunities for the development of Micro, Small and Medium Enterprises (MSMEs) in West Java. With a very large number, MSMEs in West Java have great potential to drive economic growth. However, various obstacles such as access to capital, information, and technology are still an obstacle. This research proposes the application of the Service Science framework to map the MSME ecosystem and identify opportunities for service innovation. Thus, it is expected to increase the competitiveness of MSMEs and make a greater contribution to the regional economy. This research reveals that MSMEs in West Java face significant constraints in terms of access to capital, information, and technology. Through in-depth interviews with 8 MSME owners, this research aims to understand in-depth the challenges and opportunities faced by micro, small and medium enterprises. Thematic analysis of the interview data identified a gap between the ideal conditions that MSMEs desire and the actual conditions they experience. Using the Service Quality Gap Model, this study created four action plans to improve MSMEs in West Java.  By addressing the identified gaps and encouraging collaboration between MSMEs, government, academia and industry, the Sadulur platform can catalyze the sustainable growth and development of MSMEs in West Java. These gaps, which we refer to as 'customer gaps', are manifested in four main themes: 1) the potential for MSMEs to create innovative products more easily, 2) the need to develop a strong business foundation and build sustainable brand value, 3) the importance of improving business processes and management to increase efficiency, and 4) the need to build good relationships with external parties to expand networks and business opportunities. These findings form the basis for formulating an action plan to improve the quality of services provided to MSMEs.